Scale-up and turbulence modelling in pipes - Loyseau, Xavier F.; Verdin, Patrick G.; Brown, L. D. (Elsevier, 2017)
Large diameter pipes are commonly used for oil and gas transportation. Experimental and numerical results, including turbulence properties, are often obtained for small diameter pipes. Only little information is available for pipes larger or equal to 200 mm. Results obtained with Reynolds Averaged Navier-Stokes (RANS) turbulence models for single phase flow in pipes of different sizes are presented and discussed. The use of non-dimensional data is usually assumed sufficient to present general information and is assumed valid for any size of pipe. The validity of such assumptions has been checked and the flow behaviour in small, medium and large pipes obtained with several of the most common RANS turbulence models, has been established under specific conditions via Computational Fluid Dynamics (CFD) techniques. Although difficulties were sometimes encountered to reproduce correctly the turbulence properties described in the literature with the turbulence models implemented in open source CFD codes, it is shown that a scaling-up approach is valid as the general flow pattern can be predicted by a non-dimensional strategy.
Keywords: CFD model; Pipe; Turbulence; Simulation; Scale-up; Non-dimensional